Respuesta :
x^3 + 4x^2 – 9x – 36
Factor out common terms in the first two terms and the last two terms
x^2 (x + 4) - 9 (x + 4)
factor out the common term (x + 4)
(x + 4) (x^2 - 9)
Rewrite
(x + 4) ( x^2 - 3^2)
Use the difference of squares
(x + 4) (x + 3) (x - 3)
Hope this helps :)
Factor out common terms in the first two terms and the last two terms
x^2 (x + 4) - 9 (x + 4)
factor out the common term (x + 4)
(x + 4) (x^2 - 9)
Rewrite
(x + 4) ( x^2 - 3^2)
Use the difference of squares
(x + 4) (x + 3) (x - 3)
Hope this helps :)
Following are the solution to the given question:
Given:
[tex]\bold{x^3 + 4x^2 -9x- 36}[/tex]
To find:
factoring by group=?
Using formula:
[tex]\bold{(a^2-b^2)=(a+b)(a-b)}[/tex]
Solution:
[tex]\to \bold{x^3 + 4x^2 -9x- 36} \\\\\to \bold{x^3 + 4x^2 -9(x+ 4)} \\\\\to \bold{x^2(x + 4) -9(x+ 4)} \\\\\to \bold{(x + 4)(x^2 -9)} \\\\[/tex]
[tex]\to \bold{(x + 4)(x^2 -3^2)} \\\\\to \bold{(x + 4)(x -3)(x+3)} \\\\[/tex]
Therefore, the final answer is "[tex]\bold{(x+4)(x-3)(x+3)}[/tex]".
Learn more:
brainly.com/question/15330038